2012
DOI: 10.1080/01904167.2012.663439
|View full text |Cite
|
Sign up to set email alerts
|

Foliar Sprays of Photosynthetic Bacteria Improve the Growth and Anti-Oxidative Capability on Chinese Dwarf Cherry Seedlings

Abstract: 2 Recently, there has been increasing attempts for photosynthetic bacteria (PSB) as foliar fertilizer in China. The biomass, net photosynthetic rate (Pn), maximal photochemical efficiency of PS II(Fv/Fm) and antioxidant isoenzymes metabolism were examined in Chinese dwarf cherry (Prunus humilis Bunge) seedlings with or without exogenous PSB application in this study. PSB sprays resulted in a significant accumulation of fresh weight and leaf area of Chinese dwarf cherry plants, accompanying with a marked increa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 40 publications
0
14
0
Order By: Relevance
“…The application of R. palustris, irrespective of root inoculation and foliar spray, has been proven to be a feasible strategy to improve the yields of crops like rice (Harada et al 2005) and Chinese dwarf cherry (Yin et al 2012). In support, the plant biomass and net photosynthetic rate of Chinese pak choi cabbage (B. chinensis L.) in this study were elevated due to the foliar spray of R. palustris.…”
Section: Promotion Effects Of R Palustris On Plant Growthmentioning
confidence: 82%
See 1 more Smart Citation
“…The application of R. palustris, irrespective of root inoculation and foliar spray, has been proven to be a feasible strategy to improve the yields of crops like rice (Harada et al 2005) and Chinese dwarf cherry (Yin et al 2012). In support, the plant biomass and net photosynthetic rate of Chinese pak choi cabbage (B. chinensis L.) in this study were elevated due to the foliar spray of R. palustris.…”
Section: Promotion Effects Of R Palustris On Plant Growthmentioning
confidence: 82%
“…Moreover, it harbors various functions including excretion of plant hormones, N-fixation, and solubilization of mineral nutrients (Kantachote et al 2005;Oda et al 2008). Those features make it feasible to be used as plant growth-promoting bacteria in agriculture (Yin et al 2012). Often, it is the case to employ the R. palustris as the root inoculant (Lee et al 2008), while the foliar application and its subsequent effect is less concerned.…”
Section: Introductionmentioning
confidence: 99%
“…suspension on mushroom cultures: spraying the bacterial suspension on casing soil and between the flushes could significantly increase the mushroom yield [13]. Yin et al also found that the fresh weight of sweet cherry was increased by foliar spraying with PPB suspension [23]. Contents of chlorophyll and soluble sugar were correlated with the intensity of photosynthesis.…”
Section: Discussionmentioning
confidence: 99%
“…When leaves are sprayed with PPB, the bacteria survive with light which is different from with dark in soil. Nevertheless, whether foliar application of PPB can result in plant-growth-promoting effects has been poorly studied [23].…”
Section: Introductionmentioning
confidence: 99%
“…In the early seedling periods, for example, C. humilis not only grows slowly, but is vulnerable to the environmental changes. In our previous studies, it was proven that foliar sprays of photosynthetic bacteria could effectively improve the growth and antioxidative capability on C. humilis seedlings (Yin et al 2011). Apart from this, at the moment there are no studies addressing the effects of drought stress on photochemical efficiency, photosynthesis and carotenoid composition of C. humilis seedlings.…”
Section: Introductionmentioning
confidence: 97%